PENGARUH INSIDER OWNERSHIP, FIRM SIZE, FIRM GROWTH, DAN BUSINESS RISK TERHADAP KEBIJAKAN HUTANG PADAPERUSAHAAN PERBANKAN GO PUBLIC DI BURSA EFEK INDONESIA - Reji Hendria; Muhammad Rasuli; Rofika - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study was to examine the influence of insider ownership, firm size, firm growth and business risk on debt policy. This study is a replication of the study Murni and Andriana (2007). It is also intended to test the results of previous studies in different contexts. The population in this study is a banking company that is listed on the Indonesia Stock Exchange from 2010 until 2012. From sampling criteria specified, acquired 10 banking companies can be said to be worthy of being a sample of annual reports from 2010 to 2012. Processing of the data in this study using multiple regression analysis models with SPSS 17.0 The results show that insider ownership, firm growth and business risk has no effect on debt policy. Conversely firm size has an influence on debt policy.Keywords: insider ownership, firm size, firm growth, business risk and debt policy.